Intuitionistic Fuzzy Contra Weakly Generalized Closed Mappings - N. Sangeetha, R. Krishna Moorthy, S. Meena piyadarshini (International Journal of Advanced Science and Technology, 2020)
The purpose of this paper is to introduce and study the concepts of intuitionistic fuzzy contra weakly generalized closed mappings, intuitionistic fuzzy almost contra weakly generalized closed mappings and intuitionistic fuzzy contra weakly generalized * closed mappings in intuitionistic fuzzy topological space. Some of their properties are explored.